The Effect of Calcium Carbonate and Cholecalciferol on Pharmacokinetic Interaction of 99mTc-CTMP Radiopharmaceuticals for Bone Scanning in Rats (Rattus norvegicus) - I. Mahendra; I. Daruwati; T. H. Ambarwibawa; W. Nuraeni (Atom Indonesia, 2018)
Hypocalcemia is one of manifestation of bone metastases which could be treated  using calcium carbonate and cholecalciferol. Tc-99m radiolabeled 1,4,8,11-tetraazacyclo tetradecyl-1,4,8,11-tetramethylene phosponic acid(against 99mTc-CTMP)on the other hand is a radioactive complex compound which has an affinity toward bone. Therefore, it could be used as bone tracer (radiopharmaceutical) in bone imaging.However, there has been a concern regarding the use 99mTc-CTMPon patients who have been treated with calcium carbonate and cholecalciferol. In this circumstance 99mTc-CTMPcould interact withcalcium carbonate and cholecalciferol and it might then interefere with the imaging results. Therefore, the aim of this study was to determine the pharmacokinetic behavior of 99mTc-CTMP in rats (Rattus norvegicus)that had been previously treated with calcium carbonate and cholecalciferol. The pharmacokineticstudies were performed using four groups of animal modeland each groups consists of three rats. The groups were classified as control (I), rats treated with calcium carbonate (II), rats treated with cholecalciferol (III), and rats treated with both calcium carbonate and cholecalciferol (IV). After the rats were treated for 3 days,99mTc-CTMP radiopharmaceutical was injected through a tail vein of each rat. At specific time intervals after 99mTc-CTMP administration, blood wasthen extracted from the tail, weighedand counted using a single channel analyzer. The percentage of radioactivity in blood at a certain interval wasthen calculated to determine the distribution half-time and the elimination half-time. Thedistribution half-time of group I, II, II, and IV were 0.43+0.13, 0.25+0.18, 0.32+0.10, and 0.47+0.07 hours, respectively, while the elimination half-time were 2.56+0.18, 4.48+0.56, 4.47+1.13, 6.19+1.97 respectively. The results of T-test showed that there was no significant difference of distribution half-time between the three treated groups and the control group. However, there was significant difference of elimination half-time between the three treatment groups and control. This research showed that giving calcium carbonate or, cholecalciferol, and both for 3 days prior administration of 99mTc-CTMP would mantain elimination half-time which resulted in longer excretion/ elimination time.